Pengaruh Karakteristik Good Corporate Covernance (GCG) terhadap Audit Delay pada Perbankan Syariah di Otoritas Jasa Keuangan - Wahyu Riswan; Vanica Serly (Jurnal Eksplorasi Akuntansi, 2023)
This research aims to examine the characteristics of good corporate governance sharia to audit delay. The population of this research is in the Islamic banking sector which is registered with the financial services authority (OJK) for the 2016-2020 period. The sample using the purpose sampling method with a total of 11 samples of Islamic banking companies. The data used is secondary data from the company's annual report. The analytical method used is multiple linear regression analysis. The results of this analysis show that the audit committee has a positive effect on audit delay. The Board of Commissioners has a negative effect on audit delay. ownership has a positive managerial influence on audit delay. The sharia supervisory board has no effect on audit delay.